2020
DOI: 10.21608/ajdsm.2020.25737.1028
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Incorporation of Silica and Zirconia Nanoparticles on Some Physical and Mechanical Properties of Thermoplastic Resin Material

Abstract: Objective: This study was aimed to evaluate the effect of incorporation of two-different nanoparticles (NPs); silica (SiO 2 ), and zirconia (ZrO 2 ) on flexural strength, impact strength, as well as, water sorption and solubility of thermoplastic resin material.Materials and Methods: Two nanoparticles SiO 2 -NPs, and ZrO 2 -NPs (Nano-gate Company, Egypt) were incorporated into thermoplastic resin with different concentration (1.5 and 7 wt.%). This study was divided into five main groups; unmodified "control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The presence of fillers causes the separation of the polymer chains further apart from each other and increasing spaces between the polymer chains which facilitate water penetration due to the small size of water molecules (3) . Also, fillers addition may contribute to degree of denture porosity which increases water sorption (9,18) .This result was in agreement with a study that evaluate the effect of filler reinforcement of acrylic denture base material on water sorption, dimensional changes and transverse strength (14) , as well as another two studies that reported an increase in water sorption within the limit of ADA specifications (11) .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The presence of fillers causes the separation of the polymer chains further apart from each other and increasing spaces between the polymer chains which facilitate water penetration due to the small size of water molecules (3) . Also, fillers addition may contribute to degree of denture porosity which increases water sorption (9,18) .This result was in agreement with a study that evaluate the effect of filler reinforcement of acrylic denture base material on water sorption, dimensional changes and transverse strength (14) , as well as another two studies that reported an increase in water sorption within the limit of ADA specifications (11) .…”
Section: Discussionsupporting
confidence: 90%
“…Nanotechnology is applied in the field of prosthodontics for material improvement purposes to enhance the properties and behavior of PMMA (9,10) depending on several features including polymerparticle interface, particle size and shape, fabrication technique, and particle dispersion in the PMMA matrix (11) . One of the recent approaches for enhancement of acrylic resins properties is the addition of zirconium oxide as nanofillers.…”
Section: Introductionmentioning
confidence: 99%